Autoclave-assisted synthesis of AgNPs in Z. officinale extract and assessment of their cytotoxicity, antibacterial and antioxidant activities - Kalantari, Katayoon; Afifi, Amalina Muhammad; Moniri, Mona; Moghaddam, Amin Boroumand; Kalantari, Alireza; Izadiyan, Zahra (Institution of Engineering and Technology, 2019)
In this study, the authors synthesised silver nanoparticles (AgNPs) using autoclave as a simple, unique and eco-friendly approach. The effect of Zingiber officinale extract was evaluated as a reducing and stabiliser agent. According to transmission electron microscopy results, the AgNPs were in the spherical shape with a particle size of ∼17 nm. The biomedical properties of AgNPs as antibacterial agents and free radical scavenging activity were estimated. Synthesised AgNPs showed significant 1,1-diphenyl-2-picryl-hydrazyl free radical scavenging. Strong bactericidal activity was shown by the AgNPs on Gram-positive and Gram-negative bacteria. A maximum inhibition zone of ∼14 mm was obtained for epidermidis at a concentration of 60 μg/ml for sample fabricated at 24 h. The AgNPs also showed a significant cytotoxic effect against MCF-7 breast cancer cell lines with an half maximal inhibitory concentration value of 62 μg/ml in 24 h by the MTT assay. It could be concluded that Z. officinale extract can be used effectively in the production of potential antioxidant and antimicrobial AgNPs for commercial application. © The Institution of Engineering and Technology 2018.